Ny Frysk Lieteboek. [Fen P.J. Troelstra en P.H. de Groot]. Mei sangen fen: G. Andriesse, J.D. Baarda, J.G. van Blom e.a. Meiwirker for de muzyk: M. de Boer, W. Brandenburg, A.L. ?ierret de Cornillon e.a (Hearrenfoan, 1886)
Met muz.